Direct Oral Anticoagulants in Patients With ESRD and Kidney Transplantation - Nicholas W. Lange; Justin Muir; David M. Salerno (Kidney International Reports)
Direct oral anticoagulant (DOAC) use has significantly increased because major medical organizations endorse their role for conditions in which anticoagulation is indicated. Owing to important pharmacokinetic properties, the use of apixaban and rivaroxaban requires careful consideration in at-risk populations such as those with kidney disease. Both apixaban and rivaroxaban undergo some degree of renal elimination, and thus total drug exposure is increased in patients with renal insufficiency and/or those undergoing renal replacement therapy (RRT). The available clinical trial and real-world data in this population suggests that apixaban is likely at least comparably effective as warfarin at preventing thromboembolic events and is likely safer when evaluating bleeding risk. Rivaroxaban data is more limited, and the reported results are more discordant. Both apixaban and rivaroxaban have been used successfully in patients with end-stage renal disease (ESRD) undergoing kidney transplant listing as well as in the posttransplant setting. Prospective clinical trials evaluating the safety and efficacy of apixaban and rivaroxaban in various conditions where anticoagulation is indicated should include patients with ESRD and kidney transplant recipients to help further define the role that these important novel agents should play in these complex patient populations.